The role of community health worker in disseminating information about the main cancers of interest in basic care (Research, Society and Development, 2021)
This work aims to evaluate the previous knowledge of community health workers (CHW) working in Belém-Pará on the main types of cancer in primary care (PC). For this, a cross-sectional, descriptive study was carried out, in which 66 CHW participated, from six family health units in the administrative district of Guamá. In order to assess knowledge, a questionnaire was applied with objective questions addressing the axes: socioeconomic and demographic of the participants; previous knowledge about the pathophysiology of cancer; prevention and risk factors of major cancers in PC and levels of organization of Oncology Care. Among the results, it was found that most respondents knew the pathophysiology, as well as the correct definition of metastasis (87.88%). Regarding the cancer prevention aspect, 95.45% indicated measures or risk factors that are related to the development of the disease. However, few distinguished the levels of specialized care in oncology and their duties; as well as the periodicity and age group involved in screening for breast cancer (27.27%) and cervix (30.30%), that is, only a minority claimed to know the proper conduct for screening breast and cervix cancer according to the Ministry of Health. In addition, having a family member with cancer was statistically relevant as to the number of correct statements (p